Sistem Monitoring Kapasitas dan Laju Tetesan Cairan Infus Berbasis Nirkabel - Kartika Mulya Wati Ningsih; Achmad Setiawan; Kusno Suryadi (Journal of Innovative and Creativity, 2025)
This research aims to design and develop a wireless-based monitoring system for the capacity and drip rate of infusion fluids to improve the quality of patient care and the efficiency of medical personnel. This system is designed to be able to provide accurate and real-time information regarding infusion status via wireless technology. The hardware uses a NodeMCU ESP8266 as the main microcontroller combined with a YZC-133 type load cell sensor with a capacity of 1 kg and an HX711 module to measure the weight of the infusion fluid, and an optocoupler sensor to detect fluid drops. Data is displayed locally on a 16x2 LCD and remotely via a web server. The software system uses MongoDB as a NoSQL database that receives sensor data via HTTP protocol to an Express.js-based web server, with a PHP-based web interface. The results show that the system is able to perform well. The load cell sensor provides stable readings and is close to the actual value after calibration, while the optocoupler sensor detects liquid drops with an accuracy of approximately 95% compared to manual counting. Data is displayed in real-time on the LCD, serial monitor, and web server, and supports multi-device monitoring. The visual warning feature in the form of a red color change on the Device ID works effectively when the infusion capacity is less than 20%.